Comparative Study Between Budgeted and Actual Total Revenue, Total Expenditure of Sri Lanka - Anojan, V.; Nimalathasan, B. (International Journal of Accounting and Financial Reporting, 2018)
The main aim of this study is to find out mean difference between budgeted total revenue, expenditure and actual total revenue and expenditure of Sri Lanka from 2005 to 2017. Budget deficit is a major problem in Sri Lanka. Budget deficit of the country is increasing in every year. Every country is trying to reduce the budget deficit and it has budget as key controlling tool. If any country is unable to meet its budget for continuous and longer period of time, it will create vital economic problem for that country. According to annual report of Sri Lanka (2017), Sri Lanka had actual total revenue lower than budgeted total revenue as well as Sri Lanka had actual total expenditure lower than budgeted total expenditure. Budgeted revenue and actual revenue were as respectively LKR 1,913,650 and 1,845,017 million. Further budgeted expenditure and actual expenditure were as respectively LKR 2,962,211 and 2,603,105 million. Data of this study has been analyzed by using many statistical tools such as mean, standard deviation and independent samples t-test. The statistical results of this study reveals that there is no significant mean difference between budgeted revenue, expense and actual revenue, expense of Sri Lanka from 2005 to 2017. Sri Lanka had tax revenue, non-tax revenue and total revenue more than budget in 2007. Sri Lanka did not meet the budgeted revenue and expense during 2005 to 2017.
Keywords: Budgeted revenue; Actual revenue; Budgeted expenditure